Thermodynamic modelling of pharmaceutical sorption in soil systems: A comparative study of batch and fixed-bed approaches - László Bauer; Zoltán Szalai; Anna Vancsik; Attila Csaba Kondor; Zoltán Dévény; Bruna Silva; Lili Szabó (Ecotoxicology and Environmental Safety, 2025)
In agricultural areas, daily and seasonal temperature fluctuations can swiftly alter the mobility of pharmaceuticals in the topsoils. Therefore, developing a method that can accurately estimate the fate and transport of terrestrial contaminants like organic micropollutants is crucial. Fixed-bed systems provide a non-traditional understanding of thermodynamic calculations and better reflect the natural conditions of the soil environment than the batch method hitherto used. To demonstrate this, the sorption behaviour of three pharmaceuticals was investigated in fixed-bed and batch experiments at five pre-measured topsoil temperatures and analysed chemometrically. The fixed-bed method accurately predicts the directly relevant chemical behaviour of pharmaceuticals in the cultivated soil layer, outperforming batch methods in correlating sorption and thermodynamics data. Opposite trends were found between the standard Gibbs’ free energy (ΔG0), and maximum saturated amount, and this ΔG0 and total desorption in the fixed-bed experiment, while with batch, no significant relationship appeared. Thermodynamic results in the fixed-bed simulation indicate that 17α-ethynylestradiol and lidocaine-hydrochloride have negative entropy values owing to their physicochemical properties and competitive relationship, indicating a more specific surface reaction than diclofenac-sodium. The physical nature of sorption was observed in all cases, resulting in rapid and reversible adsorption processes. The application of fixed-bed systems instead of batch experiments provides new insights into soil-pharmaceutical interactions, demonstrating that fixed-bed systems more accurately model sorption processes. This study is the first to examine the thermodynamic aspects of pharmaceutical sorption in a fixed-bed soil system, and the findings highlight the method’s potential for improving future environmental risk assessments and guiding the development of more accurate contaminant transport models in soils.